A comparative study of Hylocereus Undatus (white dragon fruit) foliage and peel for antioxidant activity and phenolic content - Azizuddin, Nur Mardhiyyah (2018)
Hylocereus Undatus foliage is believed to have high antioxidant compared to peel of Hylocereus Undatus, which already known to contain high total phenolic content and antioxidant activities. Total phenolic content and antioxidant activity for two different solvent extractions namely; chloroform and methanol were done through Folin-Ciocalteu method and DPPH free radical scavenging assay. In determining total phenolic content, the results show that methanol extraction (30.30 ± 0.0065 mg GAE/100 g extract in foliage; 45.815 ± 0.0233 mg GAE/100g extract in peel) gives high total phenolic content than chloroform extraction (5.92 ± 0.0148 mg GAE/100 g extract in foliage; 18.89 ± 0.0055 mg GAE/100g extract in peel). However, in DPPH scavenging assay, methanol extraction (88.81 ± 0.0012 % in foliage; 97.42 ± 0.0061 % in peel) has high scavenging activity compared to chloroform extraction (38.30 ± 0.0080 % in foliage; 18.71 ± 0.0068 % in peel) which shows that antioxidant activity in chloroform solvent extraction is higher compared to methanol solvent extraction. When compared between foliage and peel, it shows that peel contain more antioxidants than foliage. This experiment has proved that Hylocereus undatus foliage has same potential as Hylocereus Undatus peel in scavenge free radical in human body.